REKONSTRUKSI PARATE EKSEKUSI HAK TANGGUNGAN ATAS TANAH Yang BERBASIS NILAI KEADILAN - Zaenal Arifin (UNISSULA, 2016)
Charging for the guarantee for creditors through the agency of mortgage right, which is based on the provisions of Law No. 4 of 1996 on Mortgage Right, has advantages where the first holder of mortgage right has the right to sell the object of mortgage right on its own power or commonly known as parate execution. However in practice, parate execution can not be carried out in line with expectations and the ideals of the establishment of these legislation. As aresult, the creditors does not get easy, legal certainty, and fairness to perform parate execution of security object. This is because parate execution meant in Law No. 4 of 1996 on Mortgage Right, construed as a substitute for hypotik grosse deed, not based on the promise to sell on its own power or “beding van eigenmactig verkoop”. Above this, required reconstruction parate execution of mortgage right, so that later can ensure easy, legal certainty, and especially givesfairness to creditors.